Body Fat and Somatotype among Malaysian School Netball Players by Playing Performance: 依據比賽表現探索馬來西亞體育學校理事會投球球員的體脂和體型 - SOH, K. G.; SOH, K. L.; O. F., Mohd Sofian; ONG, S. L.; O., O. (Asian Journal of Physical Education & Recreation, 2009)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. This research was to detennine the anthropometric profile among Under-18 year old Malaysian School Sports Council (MSSM) netball players. The anthropometric measures taken were height, body mass, body fat, and somatotype. It also investigated the differences in the anthropometric profile by playing performance. The subjects were all the 150 netball players who represented their states in the Under-18 MSSM Netball Competition in 2006・ They were divided into three categories by their playing performance - good, medium and fair. The body fat was measured using the skinfold method, and the somatotype using the Heath and Carter Somatotyping method. A significant difference was found in height by playing performance, with f-value of f(2, 147)=4.82, (p<.01). However, there were no significat differences in body mass, body fat and somatotype. The mean parameter values were height (164.79 ± 6.40 cm), body mass (58.76 ± 922 kg), body fat (1223+3.49%) and somatotype (3.29±0.99-3.52±1.48-2.69±1.18). The best players were the tallest, heaviest and had the highest body fat. They also had meso-endomorphic bodies while the lesser players were endo-mesomorphic. 此研究是測定馬來西亞體育學校理事會18歲以下投球球員的外型人體測量。人體測量度是以球員的高度、體質量、體脂和體型分類來判斷。藉此從表現狀況調查外型人體測量的差別。150名受試者都是代表各州參加2006年18歲以下馬來西亞體育學校理事會投球賽的球員，把她們的比賽表現分為三組–優良、中等和一般。研究運用測量皮膚表層的方法來固定體脂與Health-Carter人體測量方法測定體型調查。依據比賽的表現，發現球員的高度有顯著的差別(2, 147)=4.82, (p<.01)。可是，體質量、體脂和體型分類卻沒有明顯的差異。調查結果顯示各平均參數如下：高度(164.79 ± 6.40 cm)，體質量(58.76 ± 9.22 kg)，體脂(12.23±3.49%)和體型分類(3.29+0.99-3.52± 1.48-2.69± 1.18)。最優秀的球員身材較高大，擁有較高的體脂，她們多具有中胚層-內胚層體型而少數的球員是屬內胚層-中胚層體型。